Biological control of anthracnose of soybean (Research in Agriculture Livestock and Fisheries, 2015)
Soybean (Glycine max L. Meril) is one of the most important and well recognized oil seed and grain legume crops of the world. A field experiment was conducted to investigate the efficacy of BAU-Biofungicide (Trichoderma harzianum), Trichoderma based IPM Lab bio-pesticide and Bavistin against anthracnose of soybean. Five soybean cultivars viz. Sohag, BARI Soybean-6, BINA Soybean-1, BINA Soybean-2 and BINA Soybean-3 were used in this experiment. The field experiment was carried out following Randomized Complete Block Design in the field laboratory of the Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh. Anthracnose infections were found initially lower at 80 DAS, moderate infections were found at 95 DAS and the highest infections were recorded at 110 DAS in case of all the tested five soybean varieties. The highest percent reduction of anthracnose infected plants/plot over control was observed in Bavistin treated plot (76.25%) that was near to BAU Biofungicide treated plots. All the growth parameters of soybean plants such as plant height, number of pods/plant, seed weight/plant, yield/plot and yield/ha were increased significantly in BAU-Biofungicide treated plots that showed best performance in compare to IPM Lab bio-pesticide (2%) and Bavistin @ 0.2% when these treatments were applied two times with 15 days interval. However, anthracnose incidence was reduced significantly when all the treatments applied in this experiment and the effect of BAU-Biofungicide was found almost similar to Bavistin in reduction of anthracnose of soybean.Res. Agric., Livest. Fish.2(3): 419-426, December 2015